Indocyanine Green (ICG)-Guided Identification of Hypermetabolic Pancreatic Nodules in Focal Congenital Hyperinsulinism: A Case Report in a 3-Month-Old Infant - Delgado-Miguel, Carlos; Muñoz-Serrano, Antonio; Moratilla, Lucas; Sarmiento, María del Carmen; Miguel-Ferrero, Miriam; Leal, Nuria; Barrena, Saturnino; Martínez, Leopoldo (European Journal of Pediatric Surgery Reports, 2022)
Indocyanine green (ICG)-guided near-infrared fluorescence has been recently adopted in pediatric surgery, although its use in the treatment of congenital hyperinsulinism has not been reported. We present a case of focal congenital hyperinsulinism in which ICG-navigation with ICG was used during surgical treatment. A 3-month-old infant was referred to our institution from a peripheral hospital for episodes of persistent hypoglycemia since birth, with no response to intravenous treatment with diazoxide, octreotide, or hydrochlorothiazide. An abdominal positron emission tomography-computed tomography scan showed a hypermetabolic nodule in the proximal portion of the body of the pancreas, compatible with focal congenital hyperinsulinism. A heterozygous mutation in the ABCC gene (Ala1516Glyfs*19) frameshift type inherited from the father was identified, which supported this diagnosis. Laparoscopy-assisted surgery was performed with ICG-guided near-infrared fluorescence, with intravenous injection of 16 mg ICG (2 mg/mg), which allowed localization of the focal lesion in the body of the pancreas. The lesion was resected with bipolar electrocautery and intraoperative histological study confirmed complete resection. Plasma glucose values normalized 6 hours after surgery and the patient was discharged 5 days later. In conclusion, the use of ICG in the treatment of congenital hyperinsulinism helps to identify hypermetabolic pancreatic nodules, decreasing the likelihood of incomplete resection.
Keywords: congenital hyperinsulinism; indocyanine green; laparoscopy; children